2020
DOI: 10.1161/jaha.119.015177
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter–Defibrillators in Trials of Drug Therapy for Heart Failure: A Systematic Review and Meta‐Analysis

Abstract: BACKGROUND Medical therapy for heart failure with reduced ejection fraction evolved since trials validated the use of implantable cardioverter–defibrillators ( ICD s). We sought to evaluate the performance of ICD s in reducing mortality in the era of modern medical therapy by means of a systematic review and meta‐analysis of contemporary randomized clinical trials of drug therapy for heart failure with reduced ejection fraction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The reported outcomes fell into 13 unique categories of the ICF. Looking after one's health (physical activity; 15/31, 48%) [39][40][41][43][44][45][46][47][48]52,[55][56][57]64,68]; walking (12/31, 39%) [39][40][41][42][43]46,52,56,57,61,62,68]; heart rhythm (8/31, 26%) [49,51,53,54,60,66,67,69]; demographic change (mortality; 7/31, 23%) [49,51,53,54,66,67,69]; and weight maintenance functions (7/31, 23%) [42,[46][47][48]50,55,59] were the most commonly reported outcomes in the studies. Blood pressure functions (3/31, 10%)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reported outcomes fell into 13 unique categories of the ICF. Looking after one's health (physical activity; 15/31, 48%) [39][40][41][43][44][45][46][47][48]52,[55][56][57]64,68]; walking (12/31, 39%) [39][40][41][42][43]46,52,56,57,61,62,68]; heart rhythm (8/31, 26%) [49,51,53,54,60,66,67,69]; demographic change (mortality; 7/31, 23%) [49,51,53,54,66,67,69]; and weight maintenance functions (7/31, 23%) [42,[46][47][48]50,55,59] were the most commonly reported outcomes in the studies. Blood pressure functions (3/31, 10%)…”
Section: Discussionmentioning
confidence: 99%
“…In spite of comprising patients with the aforementioned specific clinical conditions, some SRs also included general populations without an applicable ICD-11 category, such as employees (3/31, 10%) [40,56,61]; students (3/31, 10%) [40,46,50]; healthy participants (2/31, 7%) [40,53]; and office workers (1/31, 3%) [40]. [49,53,66,67]. Percutaneous transluminal destruction of the arrhythmia circuit was covered by 7% (2/31) of the SRs [51,54].…”
Section: Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certainly, some classes of medical therapy and amiodarone reduce appropriate therapies but are not necessarily connected to a reduction in mortality [5] , [9] . A recent meta-analysis of 8 RCTs of drug therapy for HF, including 31,701 HF patients of whom 11.5% (3645 patients) had an ICD, demonstrated that there were no significant differences in all-cause death and sudden cardiac death in studies published either before or after 2008, and that the use of ICD was consistently associated with a reduced risk of all-cause death and sudden cardiac death, indicating that the impact of ICD on preventing sudden death was not affected by contemporary optimized medical therapy [10] . In addition, the high prevalence of HF medication in patients with electrical storm does not alter the poor outcomes [11] .…”
mentioning
confidence: 99%